Heterosis Of Yield And Its Contributing Characters Of T-Aman Rice (Oryza Sativa L) - Roy, PC; Rasul, MG; Mian, MAK; Molla, MAH (Bangladesh Journal of Plant Breeding and Genetics, 2011)
The investigation was undertaken to study heterosis over better parent, heterosis over mid parent, reciprocal effects in eight crosses, their reciprocals and parents of T-Aman rice genotypes. Maximum traits showed heterosis in desirable direction of which the hybrid FR-13A × Arman sarder performed the best towards shorter stature, yield components like tiller number, panicle length, filled grains per panicle and 100-grain weight. The hybrid FR-13A × PJT (st) showed significant and positive heterosis over better parent for plant height, number of tillers per hill, grains per panicle and yield per hill which performed the best in terms of both physical as well as yield contributing traits. Considering heterosis over mid parent, the hybrid FR-13A × Arman Sarder performed the best showing heterosis in desirable direction on maximum number of traits namely tiller number, panicle length, filled grains per panicle, harvest index and yield per tiller. Most of the hybrids showed maternal effects but the cross FR-13A × PJT (st) had no maternal effects for 100 grains weight. Key words: Rice; heterosis; better parent; mid parent; reciprocal effect DOI: http://dx.doi.org/10.3329/bjpbg.v23i1.9311 BJPBG 2010; 23(1): 1-7